Immigration and Integration Policies in UK - Anca Voicu (Romanian Journal of European Affairs, 2009)
The number of immigrants received by the United Kingdom significantly increased during the past several years. Given the set of economic and social difficulties encountered, UK created for the first time a completely original system of Nationality Legislation and started to apply a severe policy of assimilation instead of integration. UK applied the Community Law concerning immigration, asylum and free movement of workers in its national interest, the whole European construction showing the “British specificities”. Even today, there are a lot of measures to be taken in order to come to a real integration policy of immigrants.